Teaching Public International Law in Central Asia: Major Challenges, Problematic Issues, Coping Strategies and Useful Methods - Atadjanov, Rustam Bakhtiyarovich (Indonesian Journal of International Law, 2022)
Many of the challenges pertaining to the unique nature of international law that affect its efficient teaching by teachers of public international law to law university and law faculty students are very relevant to the still developing educational systems of the five Central Asian states. The article reviews, with the use of legal analytical and comparative method, those challenges including the ones that flow out of local contextual factors. Furthermore, the existing lack of private universities and availability of resources including library resources in the Central Asian region will be touched upon. The article dwells on local schools and doctrines of international law, too. Potentially useful teacher strategies which could address the existing challenges and problematic issues in terms of successfully teaching public international law are suggested. Those strategies encompass a range of innovations including but not limited to, employment of interdisciplinary approaches, connecting theory and practice in the instruction of the discipline, and others. Finally, the article provides the author’s perspective, based on his own teaching experience, as to what teaching methods could turn out to be more engaging and effective in teaching public international law in Central Asia as well as which useful skills will need to be developed in students of international law.